Answer:
1
Step-by-step explanation:
1/(1+p+q^-1)+1/(1+q+r^-1)+1/(1+r+p^-1) = 1.
Answer:
its LSA is 4800m^2.
<em><u>hope</u></em><em><u> </u></em><em><u>helps</u></em><em><u> </u></em><em><u> </u></em><em><u>uh</u></em><em><u>.</u></em><em><u>.</u></em>
Answer:
8 ================================================================ D
i might be incompetent but at least I'm not impotent
Step-by-step explanation:
Answer:
i dont know im only in 7th
Step-by-step explanation:
teehee
Answer:
Plug x-7 in for y, in the bottom equation.
x - 7 = 2 + 2x - 4
x - 7 = 2x - 2
x = 2x + 5
-x = 5
x = -5